2014
DOI: 10.1007/s10493-014-9871-2
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory bioassay of Beauveria bassiana against Tetranychus urticae (Acari: Tetranychidae) on leaf discs and potted bean plants

Abstract: Use of the mycopathogen Beauveria bassiana (strain GHA), marketed as BotaniGard(®) ES, was evaluated as a plant protection strategy against the spider mite Tetranychus urticae Koch, which is considered one of the most economically important and cosmopolitan pests of many crops. Tetranychus urticae were treated with four concentrations of conidia (1 × 10(5), 1 × 10(6), 1 × 10(7), or 1 × 10(8) conidia/ml), and virulence was assessed on mites held at four relative humidity levels (35, 55, 75, and 95 ± 2 % RH) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…The leaf circles were surrounded with cotton, moistened with distilled water, and placed over nylon foam and in a tray. The foam was kept moist with the addition of distilled water (SOARES et al, 2012;ULLAH;LIM, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaf circles were surrounded with cotton, moistened with distilled water, and placed over nylon foam and in a tray. The foam was kept moist with the addition of distilled water (SOARES et al, 2012;ULLAH;LIM, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Suspensions containing fungal conidia were obtained from the commercial products Metarril ® WP E9 and Boveril ® WP PL 63 (Koppert Biological Systems). Conidia was suspended in an aqueous solution containing 0.01% Tween ® 80 (ALMEIDA et al, 2006;ULLAH;LIM, 2015) at concentrations of 10 6 and 10 7 con.mL -1 for each isolate. Leaf circles were sprayed 100 µL of the suspensions of the isolates of M. anisopliae and B. bassiana, homogeneously.…”
Section: Methodsmentioning
confidence: 99%
“…Also, Soetopo indicated that there are many different strains of B. bassiana that exhibit considerable variation in their virulence and host ranges. More recently, Ullah and Lim tested the pathogenicity of the mycopathogen B. bassiana (strain GHA), marketed as BotaniGard ® ES (Arysta LifeScience, Tokyo, Japan), against T. urticae under laboratory conditions, and the results showed that mortality greatly increased with the conidial concentration of the product and increasing time. Time‐dependent increases in mortality were also observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Our results proved the pathogenicity of M. anisopliae against the four tested insect pest and these agree with Tamai et al (2002) who investigated the effects of 45 isolates of B. bassiana, M. anisopliae, and Paecilomyces farinosus on T. urticae and found that M. anisopliae was more pathogenic than other fungi used in the study. Bugeme et al (2014) and Ullah and Lim (2015) studied the effect of different concentrations of M. anisopliae and B. bassiana on T. urticae and noticed highest mortality rate, 98% was achieved by M. anisopliae isolate so stated that M. anisopliae is the highly effective agent that can be used in the control of both T. urticae nymphs and adults.…”
Section: Figmentioning
confidence: 99%